Indigenous chinese management philosophies: Key concepts and relevance for modern chinese firms - Garg, Ritam; Berning, Sue Claire (Indigenous Studies: Breakthroughs in Research and Practice, 2019)
Increasing internationalization of Chinese firms is continuously attracting the attention of management scholars across the world. Hence, one of the main questions in this context is whether the unique cultural concepts that are indigenous to China support or aggravate the success of Chinese firms. The main objective of this study is therefore to review the cultural aspects prevalent in China from an indigenous management perspective. In particular, we explore whether and how the ancient Chinese teachings and philosophies, such as Guanxi or Mianzi, are relevant in the modern Chinese management context. This study specifically seeks to contribute to the understanding of management culture of Chinese firms and, more generally, to cross-cultural and indigenous management research. © 2020, IGI Global.
CRIS-Team Scopus Importer:2024-12-16